Morphological and radiological study of lymph nodes in dromedaries in Algeria - Rahmoun, D. E.; Рахмун, Д. Е.; Lieshchova, M. A.; Лєщова, Марина Олексіївна; Fares, M. A.; Фарес, М. А. (Oles Honchar Dnipro National University, 2020)
Despite significant progress in the study of the subtle mechanisms of interaction between cellular and molecular elements in immune responses, the general tructure of the organs of the immune system, including the lymph node, has not been sufficiently studied, in particular in large farm animals. The lymph nodes of sexually mature camels have been studied anatomically and morpho-logically and advanced studies conducted using an X-ray system and a computer densitometer scanner with injection of a contrast medium. The topography and characteristics of the morphometric parameters (absolute and relative mass, linear measurements, volume) of certain somatic and visceral lymph nodes were determined. The mass of the lymph nodes studied varies according to the location and the interest of the organ in the satellite defense of the lymphoid system, For part of the x-ray examination of the lymph nodes, organs of large inguinal and axillary shape were selected after passing through a solution of tetraethyl-4,4-diamino-tr iphenylmethane oxalate, the lymph vessels were dilated and darkened, then iodine injections were made into the afferent lymphatic vessel of two lymph nodes; they were placed on the radiological cassette, a photograph taken on conventional radiography, for computer densito-meter, the examination was made without preparation of the organs. A capsule encompasses the parenchyma of the lymph node, whose internal structure is composed of different zones, cortical, paracortical and medullary, on the one hand the lymphatic vessels were very clear especially with the conventional radiography with preparation of the organs, while the computer densitometer clearly revealed the deep texture of the parenchyma, basing it on the intensity of emission saturation from the use of computer densitometer. Незважаючи на значний прогрес у вивченні тонких механізмів взаємодії між клітинними та молекулярними елементами в імунних реакціях, загальна структура органів імунної системи, включаючи лімфатичний вузол, недостатньо вивчена, зокрема, у великих сільськогосподарських тварин. Лімфатичні вузли статевозрілих верблюдів вивчали анатомічно та морфологічно, а також вдосконалені дослідження, проведені з використанням рентгенівської системи та комп’ютерного денситометра з ін’єкцією контрастної речовини. Топографія та характеристики морфометричних параметрів (абсолютна та відносна маса, лінійні виміри, об'єм) певних соматичних та вісцеральних лімфатичних вузлів. Маса досліджуваних лімфатичних вузлів варіюється залежно від місця розташування та зацікавленості органу в супутниковому захисті лімфоїдної системи. Для частини рентгенологічного дослідження лімфатичних вузлів, органи великої пахової та пахвової форми були відібрані після проходження через розчин тетраетил-4,4-діаміно-трифенілметан-оксалату, лімфатичні судини розширені та затемнені, потім зроблені ін'єкції йоду в аферентну лімфатичну судину двох лімфатичних вузлів; їх помістили на рентгенологічну касету, зробили фотографію, зроблену на звичайній рентгенографії, для комп’ютерного денситометра, було проведено обстеження без підготовки органів. Капсула охоплює паренхіму лімфатичного вузла, внутрішня структура якої складається з різних зон, коркової, паракортикальної та медулярної, з одного боку, лімфатичні судини були дуже чіткими, особливо при звичайній рентгенографії з підготовкою органів, тоді як комп'ютерний денситометр чітко виявила глибоку структуру паренхіми, засновуючи її на інтенсивності насичення випромінюванням від використання комп’ютерного денситометра.
Морфологічне та рентгенологічне дослідження лімфатичних вузлів у дромадерів в Алжирі
Keywords: anatomy; анатомія; topography; топографія; dromedary; дромадер; morphometric parameters; морфометричні параметри; radiology; рентгенологія; contrast agent; контрастна речовина